Structural characterization and conformational dynamics of alpha-1 antitrypsin pathogenic variants causing alpha-1-antitrypsin deficiency - Shaik, Noor Ahmad; Saud Al-Saud, Najla Bint; Abdulhamid Aljuhani, Thamer; Jamil, Kaiser; Alnuman, Huda; Aljeaid, Deema; Sultana, Nasreen; El-Harouni, Ashraf AbdulRahman; Awan, Zuhier Ahmed; Elango, Ramu; Banaganapalli, Babajan (Frontiers in Molecular Biosciences, 2022)
Background: Alpha-1 antitrypsin deficiency (AATD) is a progressive lung disease caused by inherited variants in the SERPINA1 gene. However, their actual role in maintenance of structural and functional characteristics of the SERPINA1 protein is not well characterized. Methods: The AATD causative SERPINA1 missense variants were initially collected from mutation databases, and they were filtered based on their pathogenicity potential. Then, the tertiary protein models were constructed and the impact of individual variants on secondary structure, stability, protein-protein interactions, and molecular dynamic (MD) features of the SERPINA1 protein was studied using diverse computational methods. Results: We identified that, AATD linked SERPINA1 missense variants like F76S, S77F, L278P, E288V, G216C, and H358R are highly deleterious as per the consensual prediction scores of SIFT, PolyPhen, FATHMM, and M-CAP computational methods. All these variants were predicted to alter free energy dynamics and destabilize the SERPINA1 protein. These variants were seen to cause minor structural drifts at residue level (RMSD = <2Å) of the protein. Interestingly, S77F and L278P variants subtly alter the size of secondary structural elements like beta pleated sheets and loops. The residue level fluctuations at 100ns simulation confirm the highly damaging structural consequences of all the six missense variants on the conformation dynamics of the SERPINA1 protein. Moreover, these variants were also predicted to cause functional deformities by negatively impacting the binding energy of SERPINA1 protein with ELANE ligand molecule. Conclusions: This study adds a new computational biology dimension to interpret the genotype-protein phenotype relationship between SERPINA1 pathogenic variants with its structural plasticity and functional behavior with ELANE ligand molecule contributing to the Alpha-1-antitrypsin deficiency. Our results support that AATD complications correlates with the conformational flexibility and its propensity of SERPINA1 protein polymerization when misfolded.